Vaginal transmission of cervical cancer from mothers to their newborns - Viviani Fialho, Susana Cristina Aidé; Aidé, Miguel Abdon (Brazilian Journal of Sexually Transmitted Diseases, 2021)
Transmission of maternal cancer to their offspring is extremely rare, and its occurrence is estimated to occur in roughly one baby for every 500,000 mothers with cancer, whereas one in every 1,000 live births involves a mother with cancer(1,2). In these cases, maternal cancers are presumably transmitted via hematogenous (transplacental transmission from mothers to their fetus) and often involve the spread of maternal tumor cells to the child’s different organs(3). Most cases reported are diagnosed in children under two years of age. In some cases, spontaneous tumor regression in the affected offspring is observed(4). Transplacental transmission to the fetus is probably rare due to the placental barrier and the fetal alloimmune response(5). [...]